setelah Pengaruh Relaksasi Benson Terhadap Skala Nyeri Dada Pasien Unstable Angina Pectoris (UAP) di Ruang HCU Rumah Sakit Umum Bali Royal: Pengaruh Relaksasi Benson - ariyanti, kadek juli (JURNAL MEDIKA USADA, 2024)
ABSTRACT Unstable angina pectoris has a typical chest pain complaint caused by a blockage of the coronary arteries which cause oxygen cannot be supplied to the myocardial cells resulting in anaerobic metabolism causing an accumulation of lactic acid which causes chest pain. One of the non-pharmacological therapies as supportive therapy can help the performance of gold standard therapy to reduce pain felt by Benson relaxation patients. The purpose of this study was to determine the effect of benson relaxation.This study used a quasy experimental design with a pre-post test design with control group design. This study involved 30 respondents, namely 15 respondents in the intervention group who were given Benson medication and relaxation and 15 respondents in the control group who were given medication only using a purposive sampling technique and measuring instruments used the Visual Analogue Scale before and after the intervention.The results showed that the pain scale in the intervention group before being given Benson relaxation was mostly moderate pain (60%), in the control group (73.3%) experienced moderate pain. The pain scale in the intervention group after being given Benson relaxation was mostly mild pain (93.3%), whereas in the control group (73.3%) experienced moderate pain. There was an effect of Benson's relaxation on the chest pain scale of Unstable Angina Pectoris patients with a p value = 0.001 <0.05. It is recommended that giving Benson relaxation be used as a standard for non-pharmacological pain management for patients with unstable angina pectoris.